MiR-215-5p Reduces Liver Metastasis in an Experimental Model of Colorectal Cancer through Regulation of ECM-Receptor Interactions and Focal Adhesion - Machackova, Tana; Vychytilova-Faltejskova, Petra; Souckova, Kamila; Trachtova, Karolina; Brchnelova, Dominika; Svoboda, Marek; Kiss, Igor; Prochazka, Vladimir; Kala, Zdenek; Slaby, Ondrej (Cancers, 2020)
Background: Growing evidence suggests that miR-215-5p is a tumor suppressor in colorectal cancer (CRC); however, its role in metastasis remains unclear. This study evaluates the effects of miR-215 overexpression on the metastatic potential of CRC. Methods: CRC cell lines were stably transfected with miR-215-5p and used for in vitro and in vivo functional analyses. Next-generation sequencing and RT-qPCR were performed to study changes on the mRNA level. Results: Overexpression of miR-215-5p significantly reduced the clonogenic potential, migration, and invasiveness of CRC cells in vitro and tumor weight and volume, and liver metastasis in vivo. Transcriptome analysis revealed mRNAs regulated by miR-215-5p and RT-qPCR confirmed results for seven selected genes. Significantly elevated levels of CTNNBIP1 were also observed in patients' primary tumors and liver metastases compared to adjacent tissues, indicating its direct regulation by miR-215-5p. Gene Ontology and KEGG pathway analysis identified cellular processes and pathways associated with miR-215-5p deregulation. Conclusions: MiR-215-5p suppresses the metastatic potential of CRC cells through the regulation of divergent molecular pathways, including extracellular-matrix-receptor interaction and focal adhesion. Although the specific targets of miR-215-5p contributing to the formation of distant metastases must be further elucidated, this miRNA could serve as a promising target for CRC patients' future therapeutic strategies.